Exogenous Jasmonic Acid Alleviates Blast Resistance Reduction Caused by LOX3 Knockout in Rice - Shunyu Su; Ping Tang; Rubin Zuo; Hongfeng Chen; Tianqi Zhao; Shumin Yang; Jing Yang (Biomolecules, 2023)
Lipoxygenase 3 (LOX3) is a lipid peroxidase found in rice embryos that is known to affect seed quality. Interestingly, deletion of the LOX3 gene has been shown to improve rice seed quality but decrease resistance to rice blast disease and drought. To investigate these opposing effects, we generated a LOX3 knockout construct (ΔLox3) in rice (Oryza sativa L.) plants. Blast resistance and transcription levels of rice genes in ΔLox3 rice plants and the effects of exogenous jasmonic acid (JA) on resistance and transcriptional levels of rice genes in Magnaporthe oryzae-infected ΔLox3 rice plants were further elucidated. The results showed that the ΔLox3 plants exhibited normal phenotypes, with high levels of methyl-linolenate and reactive oxygen species (ROS), and the genes involved in three Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways contributed to rice seed quality. M. oryzae-infected ΔLox3 plants exhibited serious blast symptoms with a reduced defense response but increased ROS-mediated cell death, and the genes involved in seven KEGG pathways contributed to rice seed quality. Exogenous JA treatment alleviated blast symptoms in infected ΔLox3 plants by hindering hyphal expansion, inhibiting ROS-mediated cell death, and increasing the defense response, and genes involved in 12 KEGG pathways contributed to rice seed quality. These findings demonstrate that LOX3 plays an important role in rice growth and defense, and its knockout improves rice quality at the expense of disease resistance. Exogenous JA provides a means to compensate for the reduction in defense responses of LOX3 knockout rice lines, suggesting potential applications in agricultural production.